ANALISIS HARGA MINYAK DUNIA, NEWCASTLE COAL PRICE, SUKU BUNGA, KURS DAN INFLASI TERHADAP HARGA SAHAM ITMG 2016-2022 - Panjaitan, Ricky Arianto; Karmini, Ni Luh (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2025)
The massive growth of the industrial sector has driven increasing demand for energy sources, one of which is coal. Focused public company in Indonesia in coal mining, namely PT Indo Tambangraya Megah Tbk (IDX: ITMG). The aim of this research is to analyze the relationship between world oil prices, Newcastle coal price, interest rates, exchange rates and inflation on ITMG share prices. Studies at the ITMG company which operates in coal mining for a period the 2016-2022 used monthly data to obtain a total of 84 observation. The results show that the world oil price variable has an influence significant impact on share prices. Newcastle coal price has no significant effect, Suku interest does not have a significant influence, the exchange rate and inflation have a significant influence on ITMG share prices. This research obtained R 2 test results amounted to 77.9%, which indicates that the independent variable used in the model has an influential contribution of 77.9 percent to ITMG's share price while 22.1 percent were influenced or clarified by other factors outside the research model. Keywords : World Oil Price, Inflation, Interest Rate, Exchange Rate, Stock Price